Variants in PPP3R1 and MAPT are associated with more rapid functional decline in Alzheimer's disease: The Cache County Dementia Progression Study. Issue 3 (3rd June 2013) - Peterson, David; Munger, Caitlin; Crowley, Jared; Corcoran, Chris; Cruchaga, Carlos; Goate, Alison M.; Norton, Maria C.; Green, Robert C.; Munger, Ronald G.; Breitner, John C.S.; Welsh‐Bohmer, Kathleen A.; Lyketsos, Constantine; et al.
Abstract: Background: Single‐nucleotide polymorphisms (SNPs) located in the gene encoding the regulatory subunit of the protein phosphatase 2B ( PPP3R1, rs1868402) and the microtubule‐associated protein tau ( MAPT, rs3785883) gene were recently associated with higher cerebrospinal fluid (CSF) tau levels in samples from the Knight Alzheimer's Disease Research Center at Washington University (WU) and Alzheimer's Disease Neuroimaging Initiative (ADNI). In these same samples, these SNPs were also associated with faster functional decline, or progression of Alzheimer's disease (AD) as measured by the Clinical Dementia Rating sum of boxes scores (CDR‐sb). We attempted to validate the latter association in an independent, population‐based sample of incident AD cases from the Cache County Dementia Progression Study (DPS). Methods: All 92 AD cases from the DPS with a global CDR‐sb ≤1 (mild) at initial clinical assessment who were later assessed on CDR‐sb data on at least two other time points were genotyped at the two SNPs of interest (rs1868402 and rs3785883). We used linear mixed models to estimate associations between these SNPs and CDR‐sb trajectory. All analyses were performed using Proc Mixed in SAS. Results: Although we observed no association between rs3785883 or rs1868402 alone and change in CDR‐sb ( P > .10), there was a significant association between a combined genotype model and change in CDR‐sb: carriers of the high‐risk genotypes at both loci progressed >2.9 times faster than noncarriers ( P = .015). When data from DPS were combined with previously published data from WU and ADNI, change in CDR‐sb was 30% faster for each copy of the high‐risk allele at rs3785883 ( P = .0082) and carriers of both high‐risk genotypes at both loci progressed 6 times faster ( P < .0001) than all others combined. Conclusions: We replicate a previous report by Cruchaga et al that specific variations in rs3785883 and rs1868402 are associated with accelerated progression of AD. Further characterization of this association will provide a better understanding of how genetic factors influence the rate of progression of AD and could provide novel insights into preventative and therapeutic strategies.